Factors influencing immunization record retrieval from immunization information systems among independent community pharmacies: A National Survey - Oluchukwu M. Ezeala; Nicholas P. McCormick; Christopher L. Meininger; Hannah Fish; John Beckner; David Ha; Rebecca Snead; Heather Vance; Salisa C. Westrick (Vaccine: X)
Background/objectives: Community pharmacies may not consistently check patients' immunization records from Immunization Information Systems (IIS) before administering vaccines. Therefore, this study aimed to identify key factors associated with vaccine records retrieval from IIS among community pharmacies. Methods: A cross-sectional survey of 9446 members of the United States National Community Pharmacists Association was conducted from September–November 2022. There were 492 responses (response rate 5.2 %) received. The analysis included 202 participants who provided immunization services in 2021, administered vaccines besides COVID-19 or influenza, and completed ≥80 % of the questionnaire. The dependent variable was participants' self-reported frequency of retrieving immunization records from IIS (categorized as high or low IIS users). The independent variables considered were participant/pharmacy characteristics, IIS knowledge and perceptions about innovation characteristics, process, and inner settings, as identified by the Consolidated Framework for Implementation Research. Exploratory factor analysis identified ten perception scales, and all had Cronbach's Alpha coefficient of >0.70. Results: Approximately 65 % of the respondents were high IIS users (“frequently”/“always”) while 35 % were low IIS users (“never”/“rarely”/“occasionally”). A bivariate analyses of the relationship between the dependent and independent variables indicated significant differences in job title, state requirement for documentation in IIS, and eight scales: perceived benefit of IIS in consolidating patient records, optimizing immunization service delivery process, perceived IIS usability, process of engaging staff in IIS implementation, leadership support in encouraging IIS utilization, team values, open communications, and organizational needs fulfillment. A multivariable logistic regression analysis revealed that process optimization (p = .009) and leadership support (p = .018) were the two significant predictors of being in the high IIS user group when accounting for other variables. Conclusion: Interventions to encourage independent community pharmacies to retrieve vaccine records from IIS should focus on enhancing the efficiency of the IIS process and leadership support.